The Chinese version of the Health Professional Communication Skills Scale: Psychometric evaluation - Zhong, Xiaoying; Tang, Fangmei; Lai, Dongmei; Guo, Xiujing; Yang, Xiaorong; Hu, Rong; Li, Dehua; Lu, Yongguang; Liu, Sixu; Leal-Costa, César (Frontiers in Psychology, 2023)
Objective This study aims to translate the Health Professional Communication Skills Scale (HP-CSS) into Chinese and assess its psychometric properties. Methods A total of 836 healthcare professionals were recruited. The demographic characteristics form and HP-CSS were used for data collection. The psychometric properties of HP-CSS were evaluated by examining item analysis, construct validity, known-group discriminant validity, internal consistency, and split-half reliability. Results In terms of item analysis, the critical ratio (CR) of 18 items was both >3 (CR ranging from 9.937 to 28.816), and the score of each item was positively correlated with the total score (r ranging from 0.357 to 0.778, P < 0.001). The fit indices showed that the original correlated four-factor model of HP-CSS was adequate: χ2 =722.801; df = 126; χ2/df = 5.737; RMSEA = 0.075; CFI = 0.923; NNFI = 0.908; TLI = 0.906; IFI = 0.923. In terms of known-group discriminant validity, the HP-CSS total score was related to gender, occupation, work years, and communication skill training. Cronbach's α coefficient was 0.922, and the split-half reliability was 0.865 for the total scale. Conclusion The Chinese version of the HP-CSS is a reliable and valid instrument to evaluate communication skills among healthcare professionals in China.